A long-term investigation on global automakers' patents and quality. (20th July 2009) - Lin, Liang-Hung
Adopting temporal and spatial factors, this study attempts to clarify the influence of quality management and other major determinants on innovation management. Considering the patenting activities and product quality of global vehicle manufacturers, long-term analyses demonstrate that firm quality management and the performance of technological innovation are recursively correlated. Technological innovation in year i enhances quality management in year i. Then, quality management in year i enhances technological innovation in year i + 1. Additionally, regression analyses show that automakers' technological innovations are strongly influenced by geographical location, Research and Development (R&D) expenditures and quality management performance.